Conservation and management of terrestrial mammals in Japan: its system and practices - Saitoh, Takashi; Kaji, Koichi; Izawa, Masako; Yamada, Fumio (THERYA, 2014)
Introduction: One hundred and one native terrestrial mammalian species, excluding Sirenia, Cetacea, Phocidae, and Otariidae, inhabit or inhabited Japan, and 51.5 % of them are endemic, most being forest dwellers. Four species, the wolf, the Okinawa flying fox, the Bonin Pipistrelle, and the Japanese river otter went extinct during the modern age. The relatively small extinction rate in Japan is probably because forest destruction has been limited. About two thirds of Japanese lands are still covered by forests (25.10/37.79 million ha; 66.4 % as of 2011 by Forestry Agency of Japanese Government). However, the number of species that are ranked high in conservation status is not small; 5, 15, and 8 species are ranked â€œVulnerableâ€ (VU), â€œEndangeredâ€ (EN), and â€œCritically endangeredâ€ (CR), respectively. The total number of species ranked in these three categories is 28, and the percentage (28.9 % = 28/97) is higher than the world standard. This situation may be caused by extensive construction of artificial forests from 1950â€™s to 1970â€™s, during which many natural forests were cut and transformed to man-made forests. Discussion and Conclusions: The proportion of natural forests was reduced to about 40 % of the total area of forests by 2013. The most influential laws for wildlife conservation and management in Japan are the â€œAct on the Conservation of Endangered Species of Wild Fauna and Floraâ€ and â€œWildlife Protection and Proper Hunting Actâ€. The Amami rabbit (Pentalagus furnessi), the Bonin flying fox (Pteropus pselaphon), a subspecies of Ryukyu flying fox (Pteropus dasymallus daitoensis), and two subspecies of the leopard cat (Prionailurus bengalensis iriomotensis and P. b. euptilurus) are conserved under the â€œAct on Conservation of Endangered Species of Wild Fauna and Floraâ€, whereas the conservation of many endemic terrestrial species that are ranked high in conservation status are not implemented in Japanese laws. Recently many management practices have been developed for overabundant populations of the sika deer (Cervus nippon) and the wild boar (Sus scrofa) under â€œWildlife Protection and Proper Hunting Actâ€. Key words: Amami rabbit, extinction rate, flying fox, forests, Leopard cat, management, Sika deer, wild boar, wildlife legislation